Preschool-age children’s education by art: problems and possibilities - Reda Ponelienė (Problemy Wczesnej Edukacji)
In the preschool age, one of children’s favourite activities is drawing, playing with colours, shapes, various techniques. The empirical study conducted in March, 2018 (N=182) demonstrated that respondents evaluated preschoolers’ education by art as significant for children’s educational achievements, self-development of value approaches and abilities. The teachers who participated in the research disclosed the possibilities provided by art in the educational process and pointed out the problems that hindered appropriate organization of art activities for preschoolers.